Droplet digital PCR for routine analysis of genetically modified foods (GMO) – A comparison with real-time quantitative PCR. (November 2016) - Iwobi, Azuka; Gerdes, Lars; Busch, Ulrich; Pecoraro, Sven
Abstract: Droplet digital polymerase chain reaction (ddPCR) has seen increasing applications in recent times, also in the analysis of genetically modified (GM) food and feed samples. While quantitative real-time PCR (qPCR) methods have been traditional mainstays till now, the applicability of ddPCR in routine analysis of GM food and feed has not yet been widely demonstrated. In this work, we applied ddPCR on selected GM-food and feed samples that were recently analyzed on the qPCR platform in inter-laboratory proficiency tests and showed good performance of the ddPCR method. Sometimes GM DNA at different transgene levels, useful as reference material is not readily available. Applying ddPCR, different concentrations of GM material, specifically transgene DNA at different levels (0.1–10%) useful as reference DNA, were generated from 100% non GM material and 100% transgene plant material respectively, and key performance parameters of the ddPCR assay evaluated. DdPCR performed well, indicating its suitability for the production of reference GM materials. In an expanded analysis, DNA extracted from a 100% GM reference soy plant (CV127) was appropriately diluted to low copy numbers and the absolute LOD95% determined at 2 copies (nominal value), comparing well with various published qPCR assays. In our inhibition studies, ddPCR showed a clear advantage over qPCR in SDS-inhibited samples, while its tolerance to other tested inhibitors was comparable with qPCR. Significantly, the qPCR assays demonstrated more asymmetrical amplification/inhibition with EDTA as inhibitor, with unequal inhibition in reference and transgene reactions, while inhibition was more symmetrical on the ddPCR platform. Finally, a panel of positive reference material with varying GM content from 0.1 to 10% were evaluated on the ddPCR platform and pertinent performance parameters assessed, namely, precision, accuracy and trueness of results, with good performance of the assay. Highlights: ddPCR vs. qPCR for GMO analysis. Tolerance to inhibitors must be empirically evaluated on a case-by-case basis. ddPCR for the generation of various concentrations of GM material.